Orbital Osteoblastoma: Technical Innovations in Resection and Reconstruction Using Virtual Surgery Simulation. Issue 3 (September 2016) - Novelli, Giorgio; Gramegna, Marco; Tonellini, Gabriele; Valente, Gabriella; Boni, Pietro; Bozzetti, Alberto; Sozzi, Davide
Osteoblastoma is a benign tumor of bone, representing less than 1% of bone tumors. Craniomaxillofacial localizations account for up to 15% of the total and frequently involve the posterior mandible. Endo-orbital localization is very rare, with most occurring in young patients. Very few of these tumors become malignant. Orbital localization requires radical removal of the tumor followed by careful surgical reconstruction of the orbit to avoid subsequent aesthetic or functional problems. Here, we present a clinical case of this condition and describe a surgical protocol that uses and integrates state-of-the art technologies to achieve orbital reconstruction.